I Spy with my Little Eye... a Banking Crisis - Early Warnings and Incentive Schemes in Banks - Hendrik Hakenes; Friederike Schlegel (Center for Economic Studies and ifo Institute (CESifo), 2014)
The severity and depth of the recent financial crisis hit many by surprise. Despite warning signs, the financial system seems to have been unable to aggregate existing information. As the events of Fall 2008 showed, many investors were caught off guard by the large number of banks collapsing worldwide. But what triggers an early warning, and what are the incentives to implement such a trigger? We construct a theoretical model of a bank that is financed with debt and equity, and a bank manager monitoring the bank's loan portfolio. The manager must be incentivized to warn the board before a crisis. However, we show that the board may implement a contract with insufficient incentives to communicate a warning, as refinancing conditions deteriorate when lenders notice an upcoming crisis. We discuss policies to improve information efficiency and give conditions under which regulatory measures, such as capital and liquidity regulation, increase welfare.
Keywords: G01; G21; L22; 330; banking crises; information propagation; information efficiency; incentives; compensation regulation